Practical Application of Copepod Oithona sp. Meal Supplementation in Feed as a Promoter of Survival and Growth in Vannamei Shrimp (Litopenaeus vannamei) - Heriansah Heriansah; Fathuddin; Nursyahran; Arnold Kabangnga; Buana Basir; Mesalina Tri Hidayani; Nursidi (Journal of Aquaculture and Fish Health, 2026)
The nutritional potential of copepods as live feed for larvae warrants further exploration, particularly for juvenile and adult shrimp. However, their small size presents a challenge, as larger shrimp may struggle to capture such small prey. A nutrient-based formulation approach was adopted by supplementing Oithona sp. copepod meal into vannamei shrimp (Litopenaeus vannamei) feed, and its effects on survival and growth were evaluated. A 35-day experiment was conducted in aquariums (20×20×30 cm) with an 8-liter water volume. The experimental feed was prepared by coating it with copepod meal. Four supplementation levels, each with three replicates, were tested: 0, 1, 2, and 3 g per 100 g of feed. Vannamei shrimp with an initial weight of 2.15±0.03 g and a stocking density of 16 individuals per aquarium were fed three times a day to satiation. Although the differences were not statistically significant, the survival rate of shrimp fed with supplemented diets (all 100±0.00%) was higher than that of the non-supplemented group (97.9±3.6%). In terms of growth, Absolute Weight Gain (AWG) and Specific Growth Rate (SGR) were significantly higher in the 3 g (5.27±0.02 g and 3.53±0.01% day-1), 2 g (5.13±0.08 g and 3.51±0.06% day-1), and 1 g group (4.88±0.10 g and 3.36±0.07% day-1) compared to the non-supplemented group (2.97±0.13 g and 2.48±0.11% day-1). In conclusion, the supplementation of copepod meal effectively enhanced the survival and growth of vannamei shrimp. The 3 g dose is the best dose that promotes the highest growth and survival.